Granule-Dependent Natural Killer Cell Cytotoxicity to Fungal Pathogens - Ogbomo, Henry; Mody, Christopher H. (Frontiers in Immunology, 2017)
Natural killer (NK) cells kill, or inhibit the growth of a number of fungi including Cryptococcus, Candida, Aspergillus, Rhizopus, and Paracoccidioides. Although many fungi are not dangerous, invasive fungal pathogens such as Cryptococcus neoformans, cause life-threatening disease in individuals with impaired cell-mediated immunity. While there are similarities to cell-mediated killing of tumor cells, there are also important differences. Similar to tumor killing, NK cells directly kill fungi in a receptor-mediated, cytotoxic granule-dependent manner. Unlike tumor cell killing where multiple NK cell activating receptors cooperate and signal events that mediate cytotoxicity, only the NKp30 receptor has been described to mediate signaling events that trigger the NK cell to mobilize it’s cytolytic payload to the site of interaction with C. neoformans and Candida albicans, subsequently leading to granule exocytosis and fungal killing. More recently, the NKp46 receptor was reported to bind Candida glabrata adhesins Epa1, 6, and 7 and directly mediate fungal clearance. A number of unanswered questions remain. Is only one NK cell activating receptor sufficient for signaling leading to fungal killing? Are the signaling pathways activated by fungi similar to those activated by tumor cells during NK cell killing? How do the cytolytic granules traffic to the site of interaction with fungi, and how does this process compare with tumor killing? Recent insights into receptor use, intracellular signaling and cytolytic granule trafficking during NK cell-mediated fungal killing will be compared to tumor killing, and the implications for therapeutic approaches will be discussed.